2002
DOI: 10.1002/tox.10059
|View full text |Cite
|
Sign up to set email alerts
|

Direct toxicity assessment of wastewater: Baroxymeter, a portable rapid toxicity device and the industry perspective

Abstract: Direct toxicity assessment of wastewater is becoming necessary, and new legislation may render it compulsory for the water industry. At present such assessment is performed at a laboratory away from a site, at considerable cost, and results often come too late, after a toxic event has occurred and the toxin has been released into the environment. Some of the rapid toxicity tests available today require certain conditions to function properly, or their results do not always correlate with other methods. The obj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 3 publications
0
12
0
Order By: Relevance
“…However, the system has two components: (a) the limits and resolution for the physical measurement; (b) the kinetics and transport properties in the gas, liquid and biomass; too great a reduction in headspace can lead to oxygen limitation. We have shown previously [15,16] that for the headspace/sample (V G /V L ) volumes used here and surface area of the sample/gas phase interface, the respiration is not limited by the headspace O 2 concentration during each 30 s closed respiration window, but further significant decreases in volume do appear to influence the signal measured. In previous work [15] we have also shown that simple scaling of a 'large' respirometer does not necessarily give a comparable respirometric measurement.…”
Section: Recording and Resolving The Respirometric Signalmentioning
confidence: 94%
See 3 more Smart Citations
“…However, the system has two components: (a) the limits and resolution for the physical measurement; (b) the kinetics and transport properties in the gas, liquid and biomass; too great a reduction in headspace can lead to oxygen limitation. We have shown previously [15,16] that for the headspace/sample (V G /V L ) volumes used here and surface area of the sample/gas phase interface, the respiration is not limited by the headspace O 2 concentration during each 30 s closed respiration window, but further significant decreases in volume do appear to influence the signal measured. In previous work [15] we have also shown that simple scaling of a 'large' respirometer does not necessarily give a comparable respirometric measurement.…”
Section: Recording and Resolving The Respirometric Signalmentioning
confidence: 94%
“…The microorganism pellet preparation allows reproducible respiration to be recorded immediately on contact with the sample [15,16], but the bacteria typically require 130-160 min to reach their full respiration rate, once a sample is introduced. Fig.…”
Section: Recording and Resolving The Respirometric Signalmentioning
confidence: 99%
See 2 more Smart Citations
“…In the areas of environmental protection, toxicology and drug development there are increasing demands for high-throughput functional screening methods (Rogers 1995;Paddle 1996;Ohlstein, Ruffolo et al 2000;Heck, Roy et al 2001;Croston 2002;Tzoris, Fearnside et al 2002). For monitoring of the environment, whole-cell biosensors could be more effective than physico-chemical methods to assess the global toxicity of the wide variety of chemicals that are possible pollutants (Evans, Briers et al 1986;Rogers 1995;Bousse 1996;Paddle 1996;.…”
Section: Introductionmentioning
confidence: 99%